(untitled) (Web of Teachers: Inderscience Research, 2025)
This teaching-methodical manual is written for teachers of the special education system, as well as teachers of general education schools where inclusive education has been introduced, who address the educational challenges of deaf and hard-of-hearing children. It thoroughly describes Uzbek sign language and the system for teaching it.